Knowledge, attitude and practice of oral health promoting factors among caretakers of children attending day-care centers in Kubang Kerian, Malaysia: a preliminary study - Mani, S.A.; Aziz, A.A.; John, J.; Ismail, N.M. (2010)
Background and Aim: The role of caretakers at day-care centers has become more imperative in promoting oral health care in children since many new mothers opt to work outside their homes, leaving their children at day-care centers. The aim of this study is to assess the knowledge, attitude and practice of oral health promoting factors among secondary caretakers of children attending day-care centers. Settings and Design: This was a cross-sectional exploratory study conducted among secondary caretakers in Kubang Kerian, Malaysia. Materials and Methods: Thirty-four caretakers fulfilling the inclusion and exclusion criteria participated in the study. The data were collected using a self-administered questionnaire addressing various aspects of knowledge, attitude and practice of oral health in children. Analysis was done using SPSS version 12.0. Results: The knowledge of factors causing dental caries was found to be good among majority of the caretakers, but the concepts of transmissibility of caries and effect of hidden sugars were not evident. Seventy one percent did not know that frequent bottle feeding could cause tooth decay. Attitudes seemed to be governed by the cultural practices of the region rather than the knowledge obtained. The knowledge was not translated to practice adequately. Giving sweetened liquid in bottles was practiced by 53 of the caretakers. Conclusion: Implementation of nursery-based oral health promotion programs for secondary caretakers is needed to counteract early childhood caries.